Measuring Process Factors of Fluid Reasoning Using Multidimensional Computerized Adaptive Testing. - Akhtar, Hanif; Kovacs, Kristof (Assessment, 2025)
Although many fluid reasoning (Gf) tests have been developed, there is a lack of figural tests measuring its lower-order process factors simultaneously. The present article introduces the development of the Multidimensional Induction-Deduction Computerized Adaptive Test (MID-CAT) to measure two process factors of Gf. The MID-CAT is designed to provide an instrument that is flexible, efficient, and entirely free for non-commercial use. We created 530 items and administered them to a sample of N = 2,247. Items were fitted and calibrated using the Rasch model. The results indicate that the final item pool has a wide range of difficulties that could precisely measure a wide range of test-takers' abilities. A simulation study also indicates that MID-CAT provides greater measurement efficiency than separate-unidimensional CAT or fixed-item test. In the discussion, we provide perspectives on how the MID-CAT can be used for future research.